Autologous hematopoietic cell transplantation for acute promyelocytic leukemia in second complete remission: outcomes before and after the introduction of arsenic trioxide. Issue 5 (4th May 2017) - Yanada, Masamitsu; Yano, Shingo; Kanamori, Heiwa; Gotoh, Moritaka; Emi, Nobuhiko; Watakabe, Kyoko; Kurokawa, Mineo; Nishikawa, Akinori; Mori, Takehiko; Tomita, Naoto; Murata, Makoto; Hashimoto, Hisako; et al.
Abstract: We conducted a retrospective registry-based study involving 198 patients with acute promyelocytic leukemia (APL) who underwent autologous hematopoietic cell transplantation (HCT) during second complete remission (CR2) from 1995 to 2012. Arsenic trioxide (ATO) became commercially available in Japan in December 2004, and a substantial increase in the annual numbers of transplantations has occurred since 2005. Patients transplanted after 2006 had significantly better relapse-free and overall survival than those transplanted before 2004 ( p  = .028 and p  = .027, respectively). There was a significant difference in cumulative incidence of relapse in favor of those transplanted after 2006 ( p  = .008), whereas non-relapse mortality did not differ between the two groups ( p  = .683). Our findings suggest that the introduction of ATO may have reduced post-transplantation relapse without increasing non-relapse mortality, resulting in significant improvements in overall outcomes for relapsed APL patients undergoing autologous HCT during CR2.